Aplicación de las técnicas grafo plásticas en el desarrollo psicomotriz en los niños del primer año de educación básica de la escuela fiscal mixta Doctor Manuel Benjamín Carrión Mora del cantón Machala, en el año lectivo 2012-2013. - Aguilar Peñaloza, Mabel del Cisne (2013)
This paper frames the importance of the implementation of the visual graph techniques created to reorient the management of these teachers, to the development of creativity of children in preschool, placing main beneficiaries students of the Fiscal school D. Manuel Mora Benjamin Carrion, Machala canton.